Proanthocyanidin A2 attenuates the activation of hepatic stellate cells by activating the PPAR-γ signalling pathway - Yacong Xiao; Xiujuan Li; Li Wang; Mingyue Hu; Youlin Liu (Taylor & Francis Group, 2023)
Liver fibrosis is the pathological process of chronic liver diseases induced by hepatic stellate cells. Proanthocyanidin A2 (PA2) has multiple pharmacological activities. In this study, we aimed to explore the effects of PA2 on hepatic stellate cell (HSC) activation in liver fibrosis. LX-2 cells were treated with TGF-β1 to establish a fibrosis cell model. Cell viability was evaluated using cell counting kit-8. The levels of fibrosis-related factors (collagen I, fibronectin, and α-SMA) were examined using quantitative real-time polymerase chain reaction, western blot, and immunofluorescence assay. The molecular mechanisms of PA2 were evaluated by RNA-seq, bioinformatic analysis, and western blot. The results showed that PA2 suppressed cell viability, and downregulated fibrosis-related factors induced by TGF-β1, suggesting PA2 suppressed the activation of HSCs. PA2 treatment-induced differentially expressed mRNAs are predicted to be associated with the PPAR-γ pathway. PA2 reversed the downregulation of PPAR-γ and the upregulation of phosphorylated (p)-Smad2 and Smad3. A rescue experiment illustrated that the inactivation of the PPAR-γ pathway reversed the effects of PA2 on cell viability and HSC activation. In conclusion, PA2 inhibited TGF-β1-induced activation of HSCs by activating the PPAR-γ/Smad pathway. The findings suggested that PA2 may be an effective treatment for liver fibrosis.